Neue Arten des supraspezifischen Taxons Dimina Candeze, 1863 aus Südostasien (Coleoptera: Elateridae). - Schimmel, Rainer; Platia, Giuseppe (Contributions to Entomology = Beiträge zur Entomologie, 1992)
During the study of the species of the supraspecific taxon Dimina from Himalaya regions, we have had the occasion to review further material of Dimina, collected out of this regions in south-east Asia. As a result of this study we are describing a new genus, Neodima n. gen. and 17 new species: Csikia catei n. sp., C. manipurensis n. sp., Dima niehuisi n. sp., D. pusilla n. sp., D. siamensis n. sp., Neodima sichuanensis n. sp., Penia arimotoi n. sp., P. candezei n. sp., P. horrida n. sp., P. pseudoplagiata n. sp., Platiana brevicornis n. sp., P. brevisoides n. sp., P. dolini n. sp., P. flavicollis n. sp., P. fleutiauxi n. sp., P. poggii n. sp., and P. zerchei n. sp. Nomenclatural Acts catei Schimmel & Platia, 1992 (Csikia), spec. n. manipurensis Schimmel & Platia, 1992 (Csikia), spec. n. niehuisi Schimmel & Platia, 1992 (Dima), spec. n. pusilla Schimmel & Platia, 1992 (Dima), spec. n. siamensis Schimmel & Platia, 1992 (Dima), spec. n. Neodima Schimmel & Platia, 1992 (Elateridae), gen. n. sichuanensis Schimmel & Platia, 1992 (Neodima), spec. n. arimotoi Schimmel & Platia, 1992 (Penia), spec. n. candezei Schimmel & Platia, 1992 (Penia), spec. n. horrida Schimmel & Platia, 1992 (Penia), spec. n. pseudoplagiata Schimmel & Platia, 1992 (Penia), spec. n. brevicornis Schimmel & Platia, 1992 (Platiana), spec. n. brevisoides Schimmel & Platia, 1992 (Platiana), spec. n. dolini Schimmel & Platia, 1992 (Platiana), spec. n. flavicollis Schimmel & Platia, 1992 (Platiana), spec. n. fleutiauxi Schimmel & Platia, 1992 (Platiana), spec. n. poggii Schimmel & Platia, 1992 (Platiana), spec. n. zerchei Schimmel & Platia, 1992 (Platiana), spec. n.